Management of Cutaneously Exposed Carotid Stents in Recurrent and Unresectable Head and Neck Cancer - Beer-Furlan, André; Heilingoetter, Ashley; Rayle, Christopher; O'Toole, Thomas; Nielsen, Thomas J.; Crowley, Richard Webster; Al-Khudari, Samer (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Carotid blowout syndrome (CBS) is a rare but potentially life-threatening complication of head and neck cancer (HNC) treatment. Patients with CBS are managed with covered stents, limited published information exists regarding the management of delayed complications, specifically cutaneous exposure of stents. Here, we present our experience managing cutaneously exposed carotid artery stents (CAS) in patients with recurrent and unresectable HNC.Methods A single-institution retrospective analysis was performed to identify recurrent HNC patients who underwent CAS placement for CBS and complicated with cutaneous exposure of the stent between 2014 and 2016. Medical records were reviewed with attention to treatment history, pre-, intra-, and postoperative courses, anticoagulation needs, and durability of the reconstruction.Results We identified three patients who presented with a right CAS fully exposed in a large, ulcerative wound. All patients underwent a right pectoralis major myocutaneous flap (PMMF) to cover the exposed stent within 30 days of presentation to our institution. Two of three patients attained adequate coverage of the stent for more than 30 days, while one experienced partial flap dehiscence within 12 days. Two patients developed postoperative chest hematomas, which were managed conservatively. Two of three patients were able to undergo further palliative adjuvant treatments within 60 days of the initial surgical procedure.Conclusion In this small series, durable coverage of an exposed carotid artery with PMMF was successful in two of three patients with extensive disease burden and complex prior treatment history. No mortalities occurred within 30 days postoperatively.
Keywords: head and neck cancer; carotid artery stent; carotid blowout syndrome; pectoralis major myocutaneous flap; complication